Otonomi dan Kebijakan Anggaran Pendidikan Pasca Reformasi - Chairudin, Mochamad (Proceedings of Annual Conference for Muslim Scholars, 2019)
Post-reformation is the beginning of the opening of the Regional Autonomy which has been carried out since 2001, from centralized management to decentralized, which brought big changes in the management of education. Policy changes will certainly have positive and negative impacts, including the opening of the creativity of local governments to manage education according to local abilities. However, if it is not accompanied by the empowerment of resources in the regions it will become its problems